A prospective study in the treatment of androgenic alopecia using combination of procapil, capixyl, redensyl - Bansal, Garima; Bansal, Rishi (UI Scholars Hub, 2024)
Background: Androgenic alopecia is characterized by its diffuse loss and the miniaturization of the hair. The study aimed to assess the safety and efficacy of procapil, redensyl, capixyl, bicapil, and anagain in topical hair growth serum in androgenic alopecia. Methods: A prospective study was conducted on 110 healthy subjects aged 18-60 with androgenic alopecia in the Department of Dermatology, Tundla, Etmadhpur. Each subject applied 1 ml of serum on a dry scalp and was followed up on the 4th, 8th, 12th, and 16th week. Mean, median, and standard deviation were calculated. A repeated measure of the ANOVA test followed by post-hoc pairwise comparison using the Bonferroni test was applied. JAMOVI® (Sydney, Australia) software, was used for the statistical analysis. Results: Seventy subjects completed the four follow-ups. Post hoc pair-wise comparison showed that each pair differed significantly, and an increased mean score was observed between the initial and follow-up assessments for the mean Anagen:Telogen (A:T) ratio and mean hair diameter [76.84 μm vs 77.77μm, 76.84μm vs 80.03 μm, 76.84 μm vs 82.33 μm; p<0.05]. A significant difference was found in hair density between baseline and 16th week [76.84 vs 84.60; p=0.002]. No adverse effects were observed. Conclusion: This study's results suggest that after 120 days of treatment with hair serum, it is safe and effective, improving the A:T ratio, hair density, and hair thickness and hence reducing hair fall.